(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Mobile ad-hoc network (MANET) is always remains the centre of attention for research and development of wireless network. Its dynamic nature imposes several challenges to the MANET, frequent link breakage occurs due to its dynamic nature. Hence there must be some technique which maintains the link stability in spite of mobility. A challenging problem is how to select a more reliable path from source node to destination in moderate to high level of mobility. This paper presents an reliability enhanced AODV (RE-AODV) routing protocol in which we provides stable path selection considering stable links on the basis of different factors like power of node, signal strength of node and distance between the nodes and link expiration time and also presents a modified route discovery process. We discussed and analyzed this protocol with help of example which shows improvement over existing AODV protocol. Keywords: Path Selection Factor, Reliability Pair Factor, Link Expiration Time